Konsep Tuhan Menurut Pemikiran Habib Husain Ja’far Al-Hadar dalam Buku “Tuhan Ada di Hatimu” - Syafrizal, Muhammad; Nasution, Hasyimsyah (Asian Journal of Islamic Studies and Da'wah, 2023)
The book "God is in Your Heart" offers a wonderful Islamic perspective on a number of topics. include the state of the world today, all of which can be addressed by the timeless teachings of Islam. Thus, the purpose of this study was to determine what sermon themes the book "God is in Your Heart" contains. In order to formulate the problem for this study, the researcher will examine the idea of God as it is presented in Habib Ja'far Al Hadar's book "God is in your Heart." Content analysis is the analysis method employed in this study. Descriptive analysis approaches are employed in a qualitative manner to conduct content analysis in this study. Research aimed at analyzing how the idea of divinity is presented in. The author examines the idea of God in each of the eighteen book subtitles. It is evident from the data results that the book "God is in Your Heart" contains accurate information. He maintained that the mosque is the place where Muslims should perceive God and be moved to humble themselves to Him, not the existence of God within the domed structure we call a mosque. "Who knows himself, then he knows his God" is a well-known Sufi saying that, in Habib Husein Ja'far's opinion, is crucial for humanity.